Evaluation of Curcumin (Turmeric Extract) Effect on Prevention of CIN in Patient Under Elective Coronary Angiography, a Randomized Double Blind Placebocontrolled Clinical Trial (Iranian Journal of Kidney Diseases, 2020)
Introduction. Curcumin is turmeric extract that have antiproliferative, anti-cancer, and anti-oxidant effects and has been shown that it may have reno-protective properties. This study conducted to evaluate the efficacy of curcumin in the prevention of CIN. Methods. This randomized placebo-controlled clinical trial was carried out on 138 patients with chronic stable angina scheduled for elective coronary angiography that had renal insufficiency. Patients were randomized to receive curcumin or placebo in addition to standard hydration with saline 0.9% before nonionic iso-osmolar contrast agent administration for angiography. Serum creatinine was measured 12h before, 24h and 48h after contrast injection. CIN, mainly, defined as increase in creatinine of ≥ 0.5 mg/dL or ≥ 25% from the baseline. Results. Serum creatinine change was 0.19 ± 0.31 mg/dL which was 0.22 ± 0.33 and 0.16 ± 0.29 in placebo and curcumin group, respectively. In ‘repeated measure analysis’ no statistically difference was found in serum creatinine level between pre-intervention, and 24 hours and 48 hours after intervention. CIN was occurred less frequently, though statistically insignificant, in curcumin group (22.7%) compared with placebo group (32.3%). Conclusion. It was found that although curcumin reduced the incidence of CIN, this difference was not statistically significant. It seems that, like other antioxidant substances studied in previous studies, although curcumin can reduce apoptosis and oxidative stress at cellular level, but in high risk patients for CIN, such as patients with renal insufficiency, it does not produce more protective effects than hydration with normal saline.